KOHESI LEKSIKAL DAN GRAMATIKAL PADA WACANA “GANJAR PRANOWO” DALAM KOMPAS.COM - Hayyu Annaafi; Sabardila, Atiqa (Mahakarya: Jurnal Mahasiswa Ilmu Budaya, 2023)
This article aimed to describe the form of grammatical and lexical cohesion markers in online news regarding the 2024 campaign of presidential candidate Ganjar Pranowo on Kompas.com. The design of the current study was qualitative with a descriptive approach. The data were in the form of texts taken from 10 online news about Ganjar Pranowo's presidential candidate campaign on Kompas.com during September 2023. The data collection technique used was note-taking, and the data analysis technique used in this research was the distributional method. The present results found forms of grammatical cohesion in the form of references, substitutions, ellipses and conjunctions. Meanwhile, the lexical cohesion consisted of synonymy, antonymy, repetition and collocation. Overall, the most dominant finding for grammatical cohesion markers was reference and for lexical cohesion markers was collocation.Keywords: lexical cohesion; grammatical cohesion; online news; discourse analysis